2015
DOI: 10.1097/brs.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Depression Is a Strong Predictor of Poor Lumbar Fusion Outcomes Among Workersʼ Compensation Subjects

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 26 publications
3
67
0
1
Order By: Relevance
“…Low back pain is highly associated with mental health comorbidities: stress sensitivity, poor pain copying, anxiety, psychosis spectrum, and especially with depression conditions (3,7). A number of studies have found an association between psychological factors and spine surgery results, and depression has been the most reported factor, although anxiety, stress, distress, mood, and poor cognitive functioning have also been associated with inferior results (8,13,16,25,26,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain is highly associated with mental health comorbidities: stress sensitivity, poor pain copying, anxiety, psychosis spectrum, and especially with depression conditions (3,7). A number of studies have found an association between psychological factors and spine surgery results, and depression has been the most reported factor, although anxiety, stress, distress, mood, and poor cognitive functioning have also been associated with inferior results (8,13,16,25,26,43).…”
Section: Discussionmentioning
confidence: 99%
“…Presurgical screening have been successful in establishing the relationship between particular psychological (12)(13)(14)(15)(16) and social (4,10,(17)(18)(19) issues with clinical outcomes and patient satisfaction. Different risk factors were identified to independently impact surgical outcomes: work compensation (10,17,18,20), lifestyle factors (21), expectations (22)(23)(24), depression (13,16,25), anxiety (26), substance use and abuse (27,28), and preoperative education (29,30).…”
Section: Original Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Large centers and various authors have reported that social and psychological disorders, such as anxiety, depression, hopelessness, sensitivity to stress, sexual disorders, sleep disorders, marital problems, litigation, and worker compensation occur more frequently in patients with spinal problems. 1,3,8,12,[23][24][25][26][27][28] And even more importantly, some of these factors can negatively impact surgical treatment of the spine, depression being a factor frequently studied in the psychological field 23,25 and WC the most often cited factor in the social arena.…”
Section: Discussionmentioning
confidence: 99%
“…[52] Among patients with work-related injuries, preoperative depression and preoperative opioid dependence have been associated with higher postoperative medical costs, lower return to work rates, lower work retention rates, and longer postoperative pain medication use compared to other patients. [53,54] Although additional research is needed to develop and evaluate the efficacy of specific strategies to improve perioperative outcomes, conducting a holistic evaluation of every patient should enable nurses to recognize psychological and social barriers to recovery.…”
Section: Pseudarthrosismentioning
confidence: 99%